Green Ethic Behavior, Balinese Culture, and Green Marketing for Sustainable Tourism in Bali - I Made Widiantara; I Made Deddy Sandrawan; I Gusti Agung Alit Suryawati (Politeknik Negeri Bali, 2025)
This study explores the integration of green ethical behavior, Balinese culture, and green marketing strategies in sustainable tourism development in Bali through a comprehensive literature review. Employing a qualitative research design, the study analyzed 23 peer-reviewed journal articles published between 2019 and 2024, retrieved from reputable academic databases. The selected literature centered around three key themes: the role of environmental ethical behavior in tourism, incorporating Balinese cultural values in sustainable practices, and applying green marketing within the tourism sector. A systematic search was conducted using targeted keywords such as “green tourism,” “ethical behavior,” and “cultural preservation in Bali,” ensuring the relevance and quality of the sources. A narrative synthesis approach was applied to examine and interpret the data, allowing for the identification of recurring patterns, relationships, and inconsistencies. The results were organized into five overarching themes: implementation models, strengths and benefits, challenges and weaknesses, future opportunities, and policy implications. The findings suggest that Bali has cultivated a unique model of sustainable tourism by harmonizing traditional cultural philosophies with contemporary environmental initiatives. While this integration has yielded positive outcomes in promoting responsible tourism and community involvement, several obstacles remain, particularly in resource management, stakeholder coordination, and policy enforcement. This study offers valuable insights into the potential of culturally grounded strategies for advancing sustainable tourism and underscores the need for continued improvement in regulation, education, and cross-sector collaboration.